2017
DOI: 10.1037/pas0000421
|View full text |Cite
|
Sign up to set email alerts
|

Quick Delay Questionnaire: Reliability, validity, and relations to functional impairments in adults with attention-deficit/hyperactivity disorder (ADHD).

Abstract: The Quick Delay Questionnaire (QDQ) is a self-report measure of delay-related behaviors in adults, and the present study aimed at investigating the psychometric properties of QDQ scores, how well they can discriminate between ADHD adults and both clinical and nonclinical controls, as well as their relations to measures of functional impairments. In the present study, QDQ ratings, a laboratory measure of delay discounting, and ratings of functional impairments were collected from adults diagnosed with attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
(101 reference statements)
4
15
0
Order By: Relevance
“…Previous ADHD research on children has shown that there are independent effects of, but also an overlap between, different neuropsychological deficits in both clinical (Nigg et al, 2005;Sj€ owall et al, 2013;Sonuga-Barke, Bitsakou, & Thompson, 2010) and non-clinical samples (Wåhlstedt, Thorell, & Bohlin, 2009). In the few previous studies of adults that have investigated the overlap between different neuropsychological deficits, it has been shown that delayrelated behaviors and executive deficits have independent effects on ADHD in both clinical Mostert et al, 2015) and non-clinical samples (Thorell, Sj€ owall, Mies, & Scheres, 2017). This finding is in line with the dual pathway hypothesis (Sonuga-Barke, 2003).…”
Section: Overlap Between Different Neuropsychological Deficits In Adhdsupporting
confidence: 69%
“…Previous ADHD research on children has shown that there are independent effects of, but also an overlap between, different neuropsychological deficits in both clinical (Nigg et al, 2005;Sj€ owall et al, 2013;Sonuga-Barke, Bitsakou, & Thompson, 2010) and non-clinical samples (Wåhlstedt, Thorell, & Bohlin, 2009). In the few previous studies of adults that have investigated the overlap between different neuropsychological deficits, it has been shown that delayrelated behaviors and executive deficits have independent effects on ADHD in both clinical Mostert et al, 2015) and non-clinical samples (Thorell, Sj€ owall, Mies, & Scheres, 2017). This finding is in line with the dual pathway hypothesis (Sonuga-Barke, 2003).…”
Section: Overlap Between Different Neuropsychological Deficits In Adhdsupporting
confidence: 69%
“…The first showed that adults with ADHD were more likely to meet criteria for problem gambling than normal controls were, and that probability discounting, but not delay discounting, explained a significant amount of the variance in gambling-related measures after controlling for ADHD symptoms (Zhijie et al, 2013). In the second study, ratings of delay-related behavior were significantly associated with substance abuse, criminality, and money management (Thorell, Sjöwall, Mies, & Scheres, 2017).…”
Section: The Link Between Neuropsychological Deficits and Functional mentioning
confidence: 88%
“…Daily Life Functioning. We used the ADHD Daily Problem Questionnaire (ADPQ; Thorell, Sjöwall, Mies, & Scheres, 2017) to assess daily life functioning in several areas. The ADPQ is similar in design to Barkley's Functional Impairment Scale (BFIS;Barkley, 2011b), in that it contains a list of daily activities, and participants (or a close relative/friend of the patient) are asked to rate their level of functioning on a scale from 0 ("no problem") to 9 ("very severe problem").…”
Section: Ratings Of Functional Impairmentsmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with a prevalence of around 2.5% in adults ( Simon et al, 2009 ). Recently, dual pathway ( Sonuga-Barke, 2002 , 2003 ), and multiple pathway models ( Sonuga-Barke et al, 2010 ) of ADHD have been proposed based on evidence of partially dissociable patterns of deficits in distinct neuropsychological domains in individuals with ADHD (e.g., Solanto et al, 2001 ; Sonuga-Barke et al, 2010 ; Coghill et al, 2014 ; Thorell et al, 2016 ; but see Lambek et al, 2017). Two domains thought to be particularly important are executive functioning (EF) and delay aversion (DA) ( Sonuga-Barke, 2002 , 2003 ).…”
Section: Introductionmentioning
confidence: 99%